Studies on the extracellular envelope glycoprotein of maedi-visna virus - Carey, Nessa (The University of Edinburgh, 1993)
The extracellular envelope glycoprotein (gpl35) of maedi-visna virus interacts with cellular receptor molecules and is the major target of neutralising antisera in vivo. Antigenic drift of gpl35 may have an important role in viral persis tence.

In order to begin to investigate the roles of different regions of gpl35, yeast and bacterial expression systems were used to generate recombinant protein and gpl35 was expressed as 3 overlapping fragments. There have been no published reports of expression of recombinant gpl35 proteins.

By using the proteins to screen sera from infected sheep it was shown that sheep vary in the regions of gpl35 to which they mount an antibody response detectable in this system. At least 3 epitopes on gpl35 are recognised by sera from infected sheep.

The recombinant proteins were used to investigate interactions of gpl35 with cellular molecules, and as immunogens to raise gpl35-specific sera. Possible future experiments using these reagents are suggested.

gpl35 fragments derived from different viral stocks of the British isolate of maedi-visna virus were sequenced, to obtain a preliminary estimate of the extent of the variability of the gene. The data suggested the presence of both relatively conserved and variable regions in gpl35.